Program to reduce anxiety in women with breast cancer: a pilot study - Aguilera Gonzáles, Juan Pablo; González Ramírez, Javier; Ortiz Félix, Rosario Edith; Rieke Campoy, Ulises; Camargo Bravo, Adriana; Higuera Sainz, José Luis (Horizonte Sanitario, 2025)
Objective: To explore the feasibility of the intervention “Mindfulness to Reduce Anxiety in Women with Breast Cancer.” Materials and methods: A pilot study with a quasi-experimental design (pre- and post-test) was conducted. The sample consisted of women aged 30 to 69 years diagnosed with breast cancer who could read and write, had an electronic device with internet access, and had mild or higher levels of anxiety as determined by the Generalized Anxiety Scale. The intervention program lasted eight weeks and consisted of twelve sessions, eight in person and four virtual. Data were collected using a field diary, checklists, and Fabricio’s (2013) Acceptability and Feasibility Scale. The study complied with the General Health Law on Research Involving Human Beings (2024). Results: Participants had a mean age of 52.71 years and an average of 13.86 years of schooling. Regarding feasibility, participants reported that the sessions, program duration, procedures used, and program content were sufficient, as was the program’s ability to reduce anxiety. They also reported good acceptance and satisfaction with the program. However, although benefits were observed in the participants, the preliminary effect did not show significant differences in pre- and post-intervention measurements using the Wilcoxon test (p=156). Conclusions: The results of the pilot study allow us to conclude that the intervention program showed feasibility and offered benefits to its participants after eight weekly sessions. Therefore, it is recommended to test its delivery with a larger number of participants to begin exploring its effect. Keywords: Feasibility; Breast cancer; Mindfulness; Anxiety.